Edukasi Penggunaan Kontrasepsi Hormonal Terhadap Gangguan Menstruasi Pada Wanita Usia Subur Di Klinik Pratama Vina Kecamatan Medan Baru Kota MedanTahun 2023 - Asnita Sinaga; Rismalia Tarigan; Imran Surbakti; Kamelia Sinaga; Devita Purnama; Yemina Siadari (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2023)
Contraception is one way to prevent pregnancy. These efforts can be temporary, can also be permanent. Contraceptives should meet the requirements, namely safe use and can be trusted, no adverse side effects, duration of action can be adjusted according to desire, does not interfere with sexual intercourse, cheap price and can be accepted by married couples. 1 The data shows that hormonal contraceptives are most in demand in developing countries like Indonesia, however, not all contraceptives are suitable for everyone's conditions. Therefore, each individual must be able to choose suitable contraceptives. The risk of side effects can also occur in contraceptive users such as menstrual disorders, weight changes and changes in libido or sexual problems